VD_FINDINFO HC / 2014 / 237 vom 21. Februar 2014 - VD Tribunal cantonal (2014)
NOUVEAU MOYEN DE PREUVE, OBLIGATION D'ENTRETIEN, ENFANT, MAXIME INQUISITOIRE | 276 CC, 285 al. 1 CC, 285 al. 2 CC, 285 al. 2bis CC, 296 CPC (CH), 317 al. 1 CPC (CH), 318 al. 1 let. c ch. 2 CPC (CH)